Reflexões do desterro: A condição dos refugiados no Pós-Segunda Guerra Mundial a partir do caso ucraniano (TEL Tempo, Espaço e Linguagem, 2025)
The Second World War produced mass expulsions and displacements across Europe, among thousands affected not only by the calamities, but also in search of a new home, under perspectives and conditions of vulnerability, the Ukrainians were especially affected, mainly in the context of the invasion of its territory by German troops. In view of this, we seek to better understand the condition of refugees in the world and their contemporary challenges, analyzing them from the perspective of the Ukrainian case.Keywords: Ukrainians. Refugees. Modernity. Violence.